Tools and benefits of periodization: Developing an annual training plan and promoting performance improvements in athletes - Phillips, M. B.; Lockert, J. A.; Rosemond, L. D. (The Sport Journal, 2016)
All teams and athletes have goals in mind with their prospective sports. They work hard and train in the off-season to achieve their goals. Most coaches and athletes change the intensity, volume, and exercises in their workouts to improve performance. In the past, the attempts at this have been from intuitive knowledge. But over the past 20 years, many coaches have learned and utilized the periodization theory. Although periodization has become more popular, coaches and athletes still appear to struggle with completely grasping the idea of periodization.